Stratigraphy, sedimentology and resource assessment of the Lower Cretaceous Isachsen Formation: Sverdrup Basin, Ellef Ringnes Island, Nunavut, Arctic Canada ... - Tullius, Dylan Neill (Graduate Studies, 2014)
The Isachsen Formation is a Barremian to Aptian-aged fluvio-deltaic succession ranging in thickness from tens of meters to over 1400 m within the Sverdrup Basin of the Canadian Arctic Archipelago. The formation exhibits a variety of lithologies including coarse-grained quartz-arenite sandstones, fine-grained ripple laminated sandstones and siltstones, marine mudstones and coal deposits that were deposited in meandering, braided stream, coastal plain and shallow marine shelf depositional environments. This study classifies the Isachsen Formation as a mixture of recycled and craton derived sediments prograding northwest through the Sverdrup Basin with both source and reservoir potential in previously overlooked areas. Sedimentation during this time period was affected by active diapirism in some locations on Ellef Ringnes Island. Interpretations are based on observations from over 6,000 m of measured stratigraphic sections, local mapping of facies contacts, palynology, sandstone petrography and field sample ...